IMPLEMENTATION OF LEARNING MANAGEMENT SYSTEM (LMS) AT JUNIOR HIGH SCHOOL AND SENIOR HIGH SCHOOL IN SOUTH ACEH REGENCY - Yendri Farma; Akmaluddin; Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
A software program called a learning management system (LMS) offers virtualclasses for both teachers and students. LMS can be installed on the schoolwebsite and delivered to regional school networks. As a result, access toeducational resources is made simpler for junior high and senior high schoolstudents and teachers. In each academic year, junior high and senior highschools provide a large number of classes, each with a wide range of subjects.A thorough understanding of LMS features is necessary to apply the learningthat the LMS supports, allowing it to be used to support different classes anddisciplines. In order for LMS to support several classes and subjects, this studysuggests a plan for its deployment in junior high and senior high schools.